Non-Isothermal and Isothermal Kinetics in Commercial 3003 Alloys Studied By Electrical Resistivity - Luiggi A, Ney J (Ciencia)
Non-isothermal and isothermal transformation kinetics in commercial 3003 alloys were monitored by electrical resistivity p using homogenised samples for different heating rates and different ageing temperatures. In the non-isothermal case, as the temperature increases from room temperature to 615°C, p decreases to different stages until a minimum value, then grows up to a resistivity value near that of the solid solution, the position and magnitude of the minimum depending on the heating rate. Three different transformation processes are identified. In the isothermal case, which was studied at ageing temperatures between 350°C and 550°C, p decreases just up to a plateau, this plateau being more important when the ageing temperature is lower. The isothermal and non-isothermal transformation kinetics were analysed using iso-conversional techniques, obtaining in the isothermal case a decrease of the apparent activation energy between 160 and 80 kJ/mol. The non-isothermal activation energy for the formation of the equilibrium phase at high temperatures was parametrically evaluated, our non-isothermal results for particular values of the N parameter and the transformed fraction being in agreement with energies obtained using the Kissinger relation